Emotional Reactivity and Regulation in Anxious and Non-anxious Youth: A Cell-Phone Ecological Momentary Assessment Study - Tan, Patricia Z. (2011)
BACKGROUND: Reviews have highlighted anxious youths’ affective disturbances, specifically, elevated negative emotions and reliance on ineffective emotion regulation strategies. However, no study has examined anxious youth’s emotional reactivity and regulation in real-world contexts. METHODS: This study utilized an ecological momentary assessment approach to compare real-world emotional experiences of 65 youth with generalized anxiety disorder, social anxiety disorder, or social phobia (ANX) and 65 age-matched healthy controls (CON), ages 9–13 years. RESULTS: Hierarchical linear models revealed that ANX reported higher levels of average past-hour peak intensity of nervous, sad, and upset emotions than CON youth but similar levels during momentary reports of current emotion. As expected, ANX youth reported more frequent physiological reactions in response to a negative event; however there were no group differences in how frequently they used cognitive-behavioral strategies. Avoidance, distraction, and problem-solving were associated with the down-regulation of all negative emotions except nervousness for both ANX and CON youth; however, group differences emerged for acceptance, rumination, and physiological responding. CONCLUSIONS: In real-world contexts, ANX youth do not report higher levels of momentary negative emotions but do report heightened negative emotions in response to challenging events. Moreover, ANX youth report no differences in how frequently they use adaptive regulatory strategies but are more likely to have physiological responses to challenging events. They are also less effective at using some strategies to down-regulate negative emotion than CON youth.